Towards better livelihoods of livestock-keeping communities - Roesel, Kristina (2020)
Translate scientific evidence into sustainable changes for livestock-keeping communities in low- and middle-income countries – that is the goal the International Livestock Research Institute (ILRI) has set itself. Our author describes which approaches come to bear in this context, what the role of the communities themselves is in this process and which hurdles still have to be cleared to establish the One Health approach on a broad base.